Brave Irene - Steig, William, 1907-2003. (New York : Farrar, Straus, Giroux, 1986)
Plucky Irene, a dressmaker's daughter, braves a fierce snowstorm to deliver a new gown to the duchess in time for the ball.
Wilson's Children, October 2010.
Elem. School Library Collection, March 1998.
School Library Journal, March 2004.
Book Links (A.L.A.), November 2006.
Booklist, July 1997.
Horn Book, December 2003.
Keywords: Blizzards -- Fiction; Blizzards -- Fiction; Blizzards -- Fiction; Juvenile literature -- New York (N.Y.) -- 1986.